Review of the Capitellidae (Annelida, Polychaeta) from the Eastern Tropical Pacific region, with notes on selected species - García Garza, María Elena; De León González, Jesús Ángel (Pensoft Publishers, 2011)
The main objective of this work is to contribute to the taxonomic knowledge of the species of Capitellidae reported for the Eastern Tropical Pacific. This catalogue includes the original name of each species, new names, synonymies, type localities, the museum or institution where the type material is deposited, revision of the material reported for the region by different authors, new examined material, previous reports from other regions of the world, and comments on systematics and distributions. The catalogue lists 43 species in 19 genera. Of these, 6 species were erroneously recorded for the region (Decamastus gracilis Hartman, 1963; D. nudus Thomassin, 1970; Mastobranchus variabilis Edwing, 1984; Notomastus aberans Day, 1957; N. americanus Day, 1973; N. latericeus Sars, 1851) and 5 species are found here to be questionable records for the Eastern Tropical Pacific (Capitella capitata (Fabricius, 1780); Dasybranchus glabrus Moore, 1909; D. lumbricoides Grube, 1878; Notomastus lineatus Claparède, 1870 and N. tenuis Moore, 1909).